2009
DOI: 10.4315/0362-028x-72.3.637
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Storage Temperature and Product pH on the Survival of Listeria monocytogenes in Vacuum-Packaged Souse

Abstract: Souse is a fully cooked, ready-to-eat gelled pork product. There is a zero-tolerance policy for Listeria monocytogenes in ready-to-eat meat products. The survival and/or growth of L. monocytogenes in souse is unknown. The effectiveness of three different souse formulations (pH 4.3, 4.7, and 5.1) for controlling the growth of L. monocytogenes at two refrigerated storage temperatures (5 and 10 degrees C) was evaluated. All products were vacuum packaged. Uninoculated product was prepared as the control, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In contrast, Kim et al . () reported that souse, a specialty, gelled RTE meat made with pork trimmings and pork by‐products, did not support the growth of L. monocytogenes when the product was stored at 4 or 10C for up to 32 days. The authors attributed the inhibition of the pathogen on souse to the lower pH of the product (pH 4.3 to pH 5.1) and, in part, due to the addition of acetic acid to the formulation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Kim et al . () reported that souse, a specialty, gelled RTE meat made with pork trimmings and pork by‐products, did not support the growth of L. monocytogenes when the product was stored at 4 or 10C for up to 32 days. The authors attributed the inhibition of the pathogen on souse to the lower pH of the product (pH 4.3 to pH 5.1) and, in part, due to the addition of acetic acid to the formulation.…”
Section: Resultsmentioning
confidence: 99%